Analysing the Effect of Financial Risk Perception, Risk Tolerance on Investment Behaviour: An Empirical Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Investment decision making is a complex process that depends on several factors that vary from one individual to another. Regardless of the type of decision that is made in life, people behave differently. To distinguish between risk tolerance and risk perception, we must first define risk. Risk is, of course, uncertainty about the result. Any decision that casts doubt on at least one of the possible outcomes is risky. Perception is the assessment of a level of risk which usually involves an understanding of the situation, that is, there is an explanation for objective reality. Risk tolerance is the level at which an individual is willing to accept the risks associated with investments. This paper determines the relation between risk perception, risk tolerance and investment behaviour using inferential statistical analysis and draws the conclusions from the obtained results